Post-translational modifications of protein and lung cancer - Zhao, Ying; Song, Xiaoyu; Luo, WenFeng; Xie, Fangmei; Shen, Jian; He, JinHua; Han, Zeping; Huang, Jinju (Frontiers in Oncology, 2025)
Post-translational modifications (PTMs) represent a pivotal regulatory mechanism in cellular processes, wherein the addition or removal of specific functional groups to amino acid residues dynamically modulates protein activity, subcellular localization, expression levels, and interactions with other biomolecules. Key PTMs, including phosphorylation, acetylation, methylation, glycosylation, ubiquitination, and emerging types like succinylation and crotonylation, exponentially diversify the proteome’s functional landscape. In lung cancer, PTMs orchestrate critical pathological processes, such as EGFR phosphorylation-driven proliferation, H3K27me3-mediated epigenetic silencing, and KEAP1 succinylation-regulated redox homeostasis. Recent advances in mass spectrometry (MS), phosphoproteomics, and epigenomic profiling have enabled systematic mapping of PTM networks, revealing their potential as diagnostic biomarkers, therapeutic targets, and predictors of drug response. This review synthesizes the mechanistic roles of PTMs in lung cancer pathogenesis and their translational applications, highlighting multi-omics integration and PTM-targeted therapies as future frontiers in precision oncology.